The Efficacy of Using Digital Comics in Reading Class to Senior High School Students - Soleman Dapa Taka (Institut Agama Islam Negeri Palopo, 2022)
This research aims at finding out the efficacy of using Digital Comics in teaching reading to senior high school students. The main question of this research: Is the use of Digital Comics effective in teaching reading to senior high school students? The research can be an addition to the persisting teaching reading of English particularly the use of the Digital Comics. This research was conducted at the tenth-grade students at SMA Kristen Mercusuar Kupang, an Indonesian senior High School. The total number of samples was 25 students. The research used a pre-experimental method with a pre-test and post-test design. The pre-test was given to find out the basic ability of the students in reading and the post-test given to find out the students’ improvement in reading after giving the treatment by using Digital Comics as media. The findings show that using the digital comics as media is effective in teaching reading to senior high school students. It is supported by the result of the significance test through SPSS 20 program that the P was 0.00. Therefore, it is recommended to use the digital comics in developing students’ competence in reading class of senior high school students.